Validation of In Vivo MRI Blood-Brain Barrier Permeability Measurements by Comparison with Gold Standard Histology - Hoffmann, Angelika (2011)
BACKGROUND AND PURPOSE: To validate the blood-brain barrier permeability measurements extracted from perfusion-weighted MRI through a relatively simple and frequently applied model, the Patlak model, by comparison with gold standard histology in a rat model of ischemic stroke. METHODS: Eleven spontaneously hypertensive rats and eleven Wistar rats with unilateral, 2h filament occlusion of the right MCA underwent imaging during occlusion, at 4h and 24h post reperfusion. BBB permeability was imaged by gradient echo imaging after the first pass of the contrast agent bolus and quantified by a Patlak analysis. BBB permeability was shown on histology by the extravasation of Evans blue on fluorescence microscopy sections matching location and orientation of MR images. Cresyl-violet staining was used to detect and characterize hemorrhage. Landmark-based elastic image registration allowed a region-by-region comparison of permeability imaging at 24 hours with Evans blue extravasation and hemorrhage as detected on histological slides obtained immediately after the 24-hour image set. RESULTS: Permeability values in the non-ischemic tissue (marginal mean±SE: 0.15±0.019ml/min·100ml) were significantly lower compared to all permeability values in regions of Evans blue extravasation or hemorrhage. Permeability values in regions of weak Evans blue extravasation (0.23±0.016ml/min·100ml) were significantly lower compared to permeability values of in regions of strong Evans blue extravasation (0.29±0.020ml/min·100ml) and macroscopic hemorrhage (0.35±0.049ml/min·100ml). Permeability values in regions of microscopic hemorrhage (0.26±0.024ml/min·100ml) only differed significantly from values in regions of non-ischemic tissue (0.15±0.019 ml/min·100ml). CONCLUSION: Areas of increased permeability measured in-vivo by imaging coincide with BBB disruption and hemorrhage observed on gold standard histology.